Wilson disease. Issue 4 (August 2020) - Aggarwal, Annu; Bhatt, Mohit
Abstract : Purpose of review: The aim of this article is to review recent developments in the areas of the disease features and treatment of Wilson disease, and survey disorders that share its pathophysiology or clinical symptoms. Recent findings: Knowledge of the clinical spectrum of Wilson disease has expanded with recognition of patients who present in atypical age groups – patients with very early onset (<5 years) and those in whom symptoms present in mid-to-late adulthood. A disease phenotype with dominant psychiatric features and increased risk of cardiac problems and various sleep disorders have been identified. In addition to a better understanding of the phenotype of Wilson disease itself, features of some related disorders ('Wilson disease-mimics') have been described leading to a better understanding of copper homeostasis in humans. These disorders include diseases of copper disposition, such as mental retardation, enteropathy, deafness, neuropathy, ichthyosis, keratoderma syndrome, Niemann–Pick type C, and certain congenital disorders of glycosylation, as well as analogous disorders of iron and manganese metabolism. Outcomes for existing treatments, including in certain patient subpopulations of interest, are better known. Novel treatment strategies being studied include testing of bis-choline tetrathiomolybdate in phase 2 clinical trial as well as various preclinical explorations of new copper chelators and ways to restore ATP7B function or repair the causative gene. Summary: Recent studies have expanded the phenotype of Wilson disease, identified rare inherited metal-related disorders that resemble Wilson disease, and studied long-term outcomes of existing treatments. These developments can be expected to have an immediate as well as a long-term impact on the clinical management of the disease, and point to promising avenues for future research.